2015
DOI: 10.3109/00365521.2015.1028994
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition impact symptoms, handgrip strength and nutritional risk in hospitalized patients with gastroenterological and liver diseases

Abstract: NIS that preclude food intake are very frequent among patients with diseases of the liver and gastrointestinal tract. Specific NIS are associated with low HGS, weight loss and being at nutritional risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 22 publications
4
8
0
Order By: Relevance
“…A previous meta-analysis reported that objective measures of physical function (i.e., GS, walking speed, chair rising, and standing balance times) were predictive factors for all-cause mortality in elderly community-dwelling populations [49]. As muscle function reacts early to nutrition deprivation, GS can be a reliable marker for nutrition status [50,51]. These observations may be linked to our current results.…”
Section: Discussionsupporting
confidence: 77%
“…A previous meta-analysis reported that objective measures of physical function (i.e., GS, walking speed, chair rising, and standing balance times) were predictive factors for all-cause mortality in elderly community-dwelling populations [49]. As muscle function reacts early to nutrition deprivation, GS can be a reliable marker for nutrition status [50,51]. These observations may be linked to our current results.…”
Section: Discussionsupporting
confidence: 77%
“…According to the data obtained by the MNA (93.2%) and SCREEN II (100%), the respondents who were in the nursing homes had a higher risk of malnutrition or suffered from malnutrition more frequently. Similar results are presented in the research of Donini and et al (22). Nutritional status might have been affected not only by reduced consumption of fruits and vegetables, but also to the other risk factors, such as poor social status and low incomes.…”
Section: Discussionsupporting
confidence: 92%
“…( 32 ) Fearon et al, ( 33 ) and Roxburgh et al, ( 34 ) attributed the cancer patients’ inadequate food intake to the tumor itself, whereas Jeffery et al, ( 18 ) and Pearce et al,( 35 ) related this to the toxicity of the treatment. Other authors ( 2 , 3 , 36 , 37 ) stated both tumor and treatment were able to impair the food intake. Energy intake of cancer patients may vary according to the type of disease, therapeutic protocol, prior nutritional status and complications; therefore each of these aspects should be evaluated individually.…”
Section: Discussionmentioning
confidence: 97%